Adverse childhood experiences in children and adolescents with sickle cell disease: A retrospective cohort study. Issue 3 (16th December 2021) - Pernell, Brandi; Nagalapuram, Vishnu; Lebensburger, Jeffrey; Lin, Chee Paul; Baskin, Monica L.; Pachter, Lee M.
Abstract: Background: Adverse childhood experiences (ACEs) are linked to poor health outcomes; however, the relationship between ACEs and health outcomes among children and adolescents with sickle cell disease (SCD) has limited documentation in the published literature. Procedure: This retrospective cohort study involved 45 children and 30 adolescents. Participants were screened using the Center for Youth Wellness ACE Questionnaire. Parents completed the questionnaire for children. Adolescents provided self‐report. ACEs were treated as continuous and categorical scales: 0–1 verus ≥2 original ACEs (individual and/or familial level); 0–1 versus ≥2 additional ACEs (community level); and 0–3 versus ≥4 expanded ACEs (original + additional). Pain and acute chest syndrome events were compared using Wilcoxon rank‐sum tests, and correlated with cumulative ACE scores using Spearman's correlation. Multivariable models were fitted to examine the association between ACEs and pain/acute chest syndrome. Results: The cumulative number of original ACEs positively correlated with acute chest syndrome events (rho = .53, p = .003) and pain (rho = .40, p = .028) among adolescents. Adolescents with ≥2 versus 0–1 original ACEs had a higher number of acute chest syndrome events (4.9 ± 2.6 vs. 1.6 ± 2.2, p = .002); however, this association was confounded by asthma. Acute chest syndrome events and hospitalizations for pain did not differ among child ACE groups. Emergency department (ED) pain visits were higher among children with ≥4 versus 0–3 expanded ACEs (1.6 ± 2.8 vs. 3.3 ± 3.2, p = .042), even after controlling for SCD genotype, asthma, disease‐modifying treatment, and follow‐up years ( p = .027). Conclusion: ACEs are linked to increased morbidity among children and adolescents with SCD. Prospective studies are needed to further understand this relationship and test ACE‐protective remedies.